Does mobile phone use in early adolescence displace enrichment, physical activity, and sleep? A longitudinal examination of the time-displacement hypothesis - Röhlke, Leo (My University, 2025)
This study empirically tests the time-displacement hypothesis, examining if early adolescents' mobile phone use displaces time spent on developmentally beneficial activities. Time displacement is often considered a key mechanism by which mobile phone use negatively impacts developmental outcomes in adolescence, but robust empirical evidence on this hypothesis is lacking. This study overcomes several methodological limitations of prior studies on time displacement through a specific research design. Using longitudinal time-use data from a sample of Australian early adolescents (ages 10–13) in combination with a weighted difference-in-differences (DID) design, the effect of first mobile phone acquisition on allocation of time to various activities is examined. The results challenge the time-displacement hypothesis, providing no evidence that early adolescents spend less time on enrichment, physical activity, or sleep after acquiring their first mobile phone. Instead, acquiring their first mobile phone is associated with a significant reduction in time spent watching TV, movies, or videos. This suggests that the historic rise in adolescent mobile phone use may partly reflect a shift away from traditional screen-based activities rather than a displacement of developmentally beneficial activities. Parental guidelines recommending later ages of mobile phone acquisition are unlikely to impact early adolescents’ engagement in non-screen activities.
Social Science Research
Keywords: Adolescents and youth; Childhood and child development; Families and relationships; Learning, education and training; Lifestyle